2009
DOI: 10.1029/2008gl036292
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of GNSS‐R delay‐Doppler maps from the UK‐DMC satellite over the ocean

Abstract: A study of the retrieval of sea surface roughness using Global Navigation Satellite System‐Reflectometry (GNSS‐R) from satellite is presented. Delay‐Doppler Maps (DDMs) from the SSTL UK‐DMC satellite are analyzed to retrieve directional Mean Square Slopes (MSSs). Results are compared to theoretically‐derived MSSs and in situ measurements from co‐located buoys of the National Data Buoy Center (NDBC), showing good agreement in most cases. Here, the whole DDM, a more complete source of information, is exploited f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(67 citation statements)
references
References 9 publications
0
67
0
Order By: Relevance
“…Among the current spaceborne techniques, global navigation satellite system reflectometry (GNSS-R) is an effective and innovative remote sensing technique for the ocean, land and cryosphere [1,2]. It can be used to derive geophysical parameters based on the GNSS L-band signals that are reflected by the Earth's surface under all weather conditions [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Among the current spaceborne techniques, global navigation satellite system reflectometry (GNSS-R) is an effective and innovative remote sensing technique for the ocean, land and cryosphere [1,2]. It can be used to derive geophysical parameters based on the GNSS L-band signals that are reflected by the Earth's surface under all weather conditions [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…An alternative signal source using Earth reflected GNSS signals as a means of sensing the ocean surface was proposed in 1988 [13]. Researchers subsequently used data from the GNSS-R experiment on the UK-DMC satellite to demonstrated that signal retrievals of sufficient signal-to-noise ratio (SNR) could be used to perform successful ocean wave and wind estimation [14] [15] [16]. These results show that it is possible to detect reflected GNSS signals from space across a range of surface wind and wave conditions using a modest instrument configuration thus enabling an alternative to active sensing ocean remote sensing using bi-statically reflected signals transmitted from global navigation satellites (Reference Figure 6).…”
Section: Application Example In Earth Weathermentioning
confidence: 99%
“…The shape of the DDM is sensitive to the roughness of the scattering surface and, through various empirical models, the ocean surface winds [2], [3]. Ocean winds can be retrieved by fitting a scattering model to DDM observations, or identifying an observable, such as trailing or leading edge slopes or DDM power average exceeding a threshold, [4], [5]. A variety of such methods have been demonstrated with airborne experiments [3], [6], and [7].…”
Section: Introductionmentioning
confidence: 97%